Repurchased, Ordered, Inherited: The Origins of Woodcut Blocks in the Königsberg Printing House of Hans Daubmann and His Heirs - Jurkowlaniec, Grażyna (Knygotyra, 2023)
Strategies adopted by the early modern printers vis-à-vis the acquisition and use of woodcut blocks depended on various internal and external factors. One might assume that the former—a printer’s personal ambitions and convictions concerning the role of illustrations in general—were in most part dependent on the latter (i.e., the economic, political or legal circumstances). Hans Daubmann, a printer active first in Nuremberg in 1547–54 and then in Königsberg in 1554–73, is an interesting case of a fairly consistent approach to illustrations, despite the diametrically different conditions in which each of his printing houses operated. In Nuremberg, he tried—but ultimately failed—to establish his professional position, struggling against tough competition and censorship, while, in Königsberg, he easily and almost immediately dominated the local market with support from the Duke of Prussia. In both places, Daubmann issued many illustrated works and invariably minimised the associated expenditures. He was exceptionally keen on repurchasing woodblocks from various sources, which was undoubtedly much cheaper than commissioning new items. Even when he chose to order new matrices, they usually reproduced popular models. This conservative strategy was preserved until the mid-17th century by Daubmann’s heirs and followers: Georg Osterberger, Johann Fabricius and Lorenz Segebade. They mostly reused these woodblocks, some heavily worn out, and only exceptionally developed the inherited stock of printing matrices.